2020
DOI: 10.1111/his.14202
|View full text |Cite
|
Sign up to set email alerts
|

Addition of the tumour–stroma ratio to the 8th edition American Joint Committee on Cancer staging system improves survival prediction for patients with oral tongue squamous cell carcinoma

Abstract: Aims One of the objectives of current research is to customise the treatment of cancer patients. The achievement of this objective requires stratification of patients based on the most significant prognostic factors. The aims of this study were to evaluate the prognostic value of the tumour–stroma ratio (TSR), defined as the proportion of tumour cells relative to surrounding stroma, in patients with oral tongue squamous cell carcinoma (OTSCC), and to develop a prognostic nomogram based on the most significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 47 publications
(102 reference statements)
1
57
0
Order By: Relevance
“…Table 1 presents the characteristics of the studies (20,(25)(26)(27)(28)(29)(30)(31)(32)(43)(44)(45)(46)(47)(48)(49)(50), including one RCT (43), three prospective cohort studies (44)(45)(46), and 13 retrospective studies (20,(25)(26)(27)(28)(29)(30)(31)(32)(47)(48)(49)(50). Eight studies were from Asia (20,30,32,43,44,46,47,50), one was Australia (45), three were from Europe (25,28,29), and five were from North America (26,27,31,48,49). The 17 studies included a total of ...…”
Section: Selection Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 presents the characteristics of the studies (20,(25)(26)(27)(28)(29)(30)(31)(32)(43)(44)(45)(46)(47)(48)(49)(50), including one RCT (43), three prospective cohort studies (44)(45)(46), and 13 retrospective studies (20,(25)(26)(27)(28)(29)(30)(31)(32)(47)(48)(49)(50). Eight studies were from Asia (20,30,32,43,44,46,47,50), one was Australia (45), three were from Europe (25,28,29), and five were from North America (26,27,31,48,49). The 17 studies included a total of ...…”
Section: Selection Of the Studiesmentioning
confidence: 99%
“…PNI is associated with the depth of invasion of OTSCC (22) and cervical lymph node involvement and might suggest consideration for elective neck dissection (23), even in stage 1 and 2 diseases (24). A significant number of recently published research has outlined the contribution of PNI to clinical outcomes in OTSCC (10,(19)(20)(21)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Some authors advocate incorporating PNI in the staging systems for OTSCC (34).…”
Section: Introductionmentioning
confidence: 99%
“…3 Interestingly, recent studies have shown that oral tongue squamous cells carcinoma (OTSCC) exhibits peculiar molecular and clinical behavior compared to OSCC from other subsites of the oral cavity. [4][5][6][7] If not properly recognized, the presence of this potential "anatomical bias" may hinder the interpretation and clinical translation of OSCC data. 8,9 The surgical resection of primary OTSCC, with or without neck dissection, is still considered the gold standard of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Oral squamous cell carcinoma encompasses cancers developing in various sites of the oral cavity, and intraoral tongue is the most commonly involved subsite, accounting for about 40% of all OSCC cases 3 . Interestingly, recent studies have shown that oral tongue squamous cells carcinoma (OTSCC) exhibits peculiar molecular and clinical behavior compared to OSCC from other subsites of the oral cavity 4‐7 . If not properly recognized, the presence of this potential “anatomical bias” may hinder the interpretation and clinical translation of OSCC data 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…However, a semi-quantitative analysis on the density value of the immuno-stains shows less expression of p53 and CK5/6 in FFPE-tissues (Figures 3 and 4). Recently, concerns have been raised regarding the irreproducibility of the immunohistochemical data for studying prognostic features in OSCC [21,22]. The 8th edition of the American Joint Committee on Cancer (AJCC) staging has reinforced focus on histo-morphological prognostic features, such as tumor stroma ratio, depth of invasion, and extranodal extension, to study the prognosis of OSCC [22].…”
Section: Discussionmentioning
confidence: 99%